2021
DOI: 10.1093/jnci/djab097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Breast Cancer Mortality in the US: Estimates From Collaborative Simulation Modeling

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has disrupted breast cancer control through short-term declines in screening and delays in diagnosis and treatments. We projected the impact of COVID-19 on future breast cancer mortality between 2020 and 2030. Methods Three established Cancer Intervention and Surveillance Modeling Network breast cancer models modeled reductions in mammography screening use, delays in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 45 publications
(41 reference statements)
2
91
1
4
Order By: Relevance
“…A recent study of the Dutch national breast screening program similarly found that pandemic-related shutdowns had a smaller impact on non-screen detected cancer incidence than screen-detected cancer incidence ( 21 ). In a prior analysis using breast cancer models from the Cancer Intervention and Surveillance Modeling network, delays in diagnostic evaluation of symptomatic women were more detrimental to long-term outcomes than delays in screening mammography, resulting in excess breast cancer mortality ( 16 ). Thus, it is reassuring that the initial delays in breast cancer diagnoses among symptomatic women have likely largely resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the Dutch national breast screening program similarly found that pandemic-related shutdowns had a smaller impact on non-screen detected cancer incidence than screen-detected cancer incidence ( 21 ). In a prior analysis using breast cancer models from the Cancer Intervention and Surveillance Modeling network, delays in diagnostic evaluation of symptomatic women were more detrimental to long-term outcomes than delays in screening mammography, resulting in excess breast cancer mortality ( 16 ). Thus, it is reassuring that the initial delays in breast cancer diagnoses among symptomatic women have likely largely resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the downstream impact of these observed delays in breast cancer screening, and it is not yet clear how these delays will ultimately impact breast cancer outcomes. Simulation models have predicted breast cancer screening delays due to the pandemic will lead to 2 487 excess breast cancer deaths in the US over 10 years (0.5% increase) ( 16 ). While the true impact on breast cancer mortality will not be known for many years, intermediate metrics such as cancer diagnosis rates are important indicators that warrant evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be impressed that the recommendation is to perform screening mammography within a reasonable timeframe, bearing in mind that older patients are at increased risk 5 . It is estimated that there will be 2,500 additional deaths due to breast cancer because of delay in screening during the COVID-19 pandemic 13 . Further, a patient in the vaccinated cohort in our study who received the Moderna vaccine on screening mammography had a mass without axillary lymphadenopathy, resulting in biopsy-proven malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…These models suggest that the number of excess breast cancer deaths due to COVID-19 impact on screening and treatment could reach 2487 over the next decade, with a 0.52% increase in breast cancer deaths between 2020 and 2030. 32 …”
Section: Best Practices To Counter Covid-19 Related Issuesmentioning
confidence: 99%
“…33 Extended hours including evenings and weekends have helped practices overcome barriers that might discourage patients from office visits. 32 …”
Section: Best Practices To Counter Covid-19 Related Issuesmentioning
confidence: 99%